Rainfall Prediction Using Data Mining techniques: A Survey (International Journal of Engineering and Computer Science, 2017)
Data Mining is study of how to determine underlying patterns in the data. Data mining techniques like machine learning, alongside the conventional methods are deployed. Different Data mining techniques like GRNN, MLP, NNARX, CART, RBF, ARIMA and so on are used for the prediction of Rainfall. In this paper, analysis of various algorithms of data mining is used for rainfall prediction model. It is difficult to name a particular algorithm is suitable for prediction. Sometimes when certain algorithms are combined, they perform better and are more effective.